Causes of death in immediate and late liver post-transplantation patients in a reference service in Santa Catarina - Knihs, Neide da Silva (2009)
Purpose: To identify causes of late and immediate death in patients submitted to liver transplantation in the period from 2002 to 2007 in a reference hospital in the state of Santa Catarina. Method: This is a retrospective, quantitative research of investigative features from August, 2002 to December, 2007. Fifty-one medical records of patients were assessed in samples evolved to death along that period. Result: Septicand hemorrhagic shock are shown as the major immediate cause to the post-operatory death, with average life expectation of 23.7 days. The major cause to the late death was septic shock, with average life expectation of 244.1 days. Related to the TRE age, deaths occurred between 40 to 60 years old with predominance of death among the masculine gender. Conclusions: It was possible to identify through the present study that the major cause of death in liver transplantation was septic shock, having as major intercurrence pneumonia. The more affected age was between 40 and 60 years old, with predominance of masculine gender.